2021
DOI: 10.3389/fnins.2021.636259
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Mouse Brain After Traumatic Brain Injury Reveals That the Angiotensin Receptor Blocker Candesartan Acts Through Novel Pathways

Abstract: Traumatic brain injury (TBI) results in complex pathological reactions, where the initial lesion is followed by secondary inflammation and edema. Our laboratory and others have reported that angiotensin receptor blockers (ARBs) have efficacy in improving recovery from traumatic brain injury in mice. Treatment of mice with a subhypotensive dose of the ARB candesartan results in improved functional recovery, and reduced pathology (lesion volume, inflammation and gliosis). In order to gain a better understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 123 publications
(154 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have reported that candesartan, one of the angiotensin receptor blockers, could reduce lesion volume and improve motor and memory function after traumatic brain injury in mice ( Villapol et al, 2012 ; Hajmohammadi et al, 2019 ; Attilio et al, 2021 ), however, the molecular mechanism is still poorly understood. To gain insight into the potential molecular basis of this drug, we conducted an integrative analysis of single-cell (GEO accession: GSE101901) and bulk RNA-seq data ( Attilio et al, 2021 ) (GEO accession: GSE163415) to analyze the cell-type-specific changes in gene expression patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that candesartan, one of the angiotensin receptor blockers, could reduce lesion volume and improve motor and memory function after traumatic brain injury in mice ( Villapol et al, 2012 ; Hajmohammadi et al, 2019 ; Attilio et al, 2021 ), however, the molecular mechanism is still poorly understood. To gain insight into the potential molecular basis of this drug, we conducted an integrative analysis of single-cell (GEO accession: GSE101901) and bulk RNA-seq data ( Attilio et al, 2021 ) (GEO accession: GSE163415) to analyze the cell-type-specific changes in gene expression patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that candesartan, one of the angiotensin receptor blockers, could reduce lesion volume and improve motor and memory function after traumatic brain injury in mice ( Villapol et al, 2012 ; Hajmohammadi et al, 2019 ; Attilio et al, 2021 ), however, the molecular mechanism is still poorly understood. To gain insight into the potential molecular basis of this drug, we conducted an integrative analysis of single-cell (GEO accession: GSE101901) and bulk RNA-seq data ( Attilio et al, 2021 ) (GEO accession: GSE163415) to analyze the cell-type-specific changes in gene expression patterns. The differential expression analysis of the bulk RNA-seq data identified a total of 438 differentially expressed genes (DEGs) between hippocampus tissues of TBI with and without candesartan treatment ( Figure 7A ), including 243 upregulated and 195 downregulated genes in samples treated with candesartan.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, previous GO-based functional analysis of differentially expressed transcripts in mice hippocampus after controlled cortical impact injury showed the association of upregulated transcripts with five GO terms associated with the regulation of immune responses, including inflammatory response and regulation of cytokine production. 44 The MoS condition had 45 upregulated processes dealing with inflammation, which was the most of all conditions. Previous reports have shown that the severity of the injury dictates the recruitment of other immune cells, explaining the dramatic increase in the number of immune cell migrations we report in the MoS condition.…”
Section: Discussionmentioning
confidence: 99%
“… 61 , 78 Some of these long-term immune and inflammation transcriptional signatures can also be modulated by drug treatment. 60 , 62 The genes and modules identified by our approach capture molecular mechanisms and represent new potential biomarkers for stage and biological pathway-specific components of recovery and lasting pathology post-TBI. Further, future studies evaluating the intersection between neurodegeneration, neuroinflammation, and neurotransmission over time may provide better insight into why behavior and, in particular, cognition shows some recovery over time, but perhaps not quite to an equivalent performance as an age-matched control.…”
Section: Discussionmentioning
confidence: 99%